As atividades náuticas em Curitiba (1886-1900) (Revista de História Regional, 2022)
This article aims to discuss the nautical experiences in Curitiba between 1886 and 1900. To achieve the objective, the sources used were the newspapers of the capital of Paraná during the investigated period. It is in the city's first park, Passeio Público, an environment designed through perceptions linked to urban beautification and advancement, that the dynamics were developed. It was possible to observe that the nautical activities were structured from the connection with the notions that valued collective health and physical strengthening, representing an ideology related to the progressive discourse aimed at the social and material development of Curitiba.